THE ROLE OF THE HEAD OF ADMINISTRATIVE OFFICE IN ADMINISTRATION TO IMPROVE CORRESPONDENCE MANAGEMENT AT MAN 1 MEDAN - Lilis Juliyanty Marbun; Rustam (SOSIOEDUKASI, 2026)
This study aims to analyze the role of the head of administration in improving correspondence governance at MAN 1 Medan. The research employed a qualitative approach with a descriptive case study design. Data were collected through observation, semi-structured interviews, and documentation involving the head of administration and administrative staff as research informants. The findings indicate that the head of administration plays a significant role in managing correspondence administration through planning, organizing, supervising, and coordinating administrative activities. The implementation of correspondence management has been carried out systematically through the processes of receiving letters, recording, disposition, distribution, and archiving both physically and digitally. In addition, the managerial role of the head of administration is reflected in task distribution based on staff competencies, administrative supervision, and evaluation activities conducted regularly to maintain the quality of administrative services. The coordinative role is demonstrated through effective communication and collaboration among administrative units, school leadership, and external institutions. However, several obstacles remain, including delays in disposition, limited digital archiving systems, and differences in staff understanding regarding correspondence classification procedures. Therefore, strengthening managerial supervision, improving staff competencies, and optimizing digital-based archiving systems are necessary to support effective, efficient, and accountable correspondence governance in madrasah administration.